Matrix computer methods of vibration analysis - Hatter, D. J. (Butterworth, 1973)
Matrix Computer Methods of Vibration Analysis is an eight-chapter introductory text to a particular technique that combines vibration analysis, matrix algebra, and computational methods. This book is emerged from a series of lectures presented at the North-East London Polytechnic.